The Political Recruitment of Prosperous Justice Party (PKS) in Takalar Election 2017 - Ardiansya, Ariyanto (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
This research aims to know the Political Recruitment of Prosperous Justice Party (PKS) in Takalar Election 2017. The research method used qualitative method by descriptive analysis. Data obtained through interviews, observation and documentation. Informant of the research, namely the Management and Sympathizers of PKS Takalar and Nasdem Party Takalar, the couple of Syamsari Kitta - Achmad Dg. Se're, Regional Election Commission of Takalar Regency.The results showed that the recruitment of PKS in Takalar Election 2017 were: first, the couple of Syamsari Kitta - Achmad Dg Se're was promoted by the PKS 4 seats coalition with the National Democratic Party (Nasdem) 2 seats in the regional election. The coalition happened because both parties agreed that the couple is able to bring thoughts or ideas of change in the process of elections battle period of 2017-2022 in Takalar Regency. Secondly, the PKS chose Syamsari Kitta because of his strong ability and strong support-bases in Takalar as well as positive electability with the community. While Ahmad Daeng Sere chose as a candidate for vice regent because he can raise the electability to fight the duet of incumbent. Both have in common with the idea of change to make Takalar much better. Third, the recruitment of Syamsari Kitta as a candidate for regional head / regent because he is a PKS cadre who has experience and capability in politics, his personality is known as an easy person to associate and communicate with the community. The quality of Syamsari Kitta as PKS cadres got positive electoral and militancy support from PKS cadres and other winning teamresearch aims to know the Political Recruitment of Prosperous Justice Party (PKS) in Takalar Election 2017. The research method used qualitative method by descriptive analysis. Data obtained through interviews, observation and documentation. Informant of the research, namely the Management and Sympathizers of PKS Takalar and Nasdem Party Takalar, the couple of Syamsari Kitta - Achmad Dg. Se're, Regional Election Commission of Takalar Regency.The results showed that the recruitment of PKS in Takalar Election 2017 were: first, the couple of Syamsari Kitta - Achmad Dg Se're was promoted by the PKS 4 seats coalition with the National Democratic Party (Nasdem) 2 seats in the regional election. The coalition happened because both parties agreed that the couple is able to bring thoughts or ideas of change in the process of elections battle period of 2017-2022 in Takalar Regency. Secondly, the PKS chose Syamsari Kitta because of his strong ability and strong support-bases in Takalar as well as positive electability with the community. While Ahmad Daeng Sere chose as a candidate for vice regent because he can raise the electability to fight the duet of incumbent. Both have in common with the idea of change to make Takalar much better. Third, the recruitment of Syamsari Kitta as a candidate for regional head / regent because he is a PKS cadre who has experience and capability in politics, his personality is known as an easy person to associate and communicate with the community. The quality of Syamsari Kitta as PKS cadres got positive electoral and militancy support from PKS cadres and other winning teamThis research aims to know the Political Recruitment of Prosperous Justice Party (PKS) in Takalar Election 2017. The research method used qualitative method by descriptive analysis. Data obtained through interviews, observation and documentation. Informant of the research, namely the Management and Sympathizers of PKS Takalar and Nasdem Party Takalar, the couple of Syamsari Kitta - Achmad Dg. Se're, Regional Election Commission of Takalar Regency.The results showed that the recruitment of PKS in Takalar Election 2017 were: first, the couple of Syamsari Kitta - Achmad Dg Se're was promoted by the PKS 4 seats coalition with the National Democratic Party (Nasdem) 2 seats in the regional election. The coalition happened because both parties agreed that the couple is able to bring thoughts or ideas of change in the process of elections battle period of 2017-2022 in Takalar Regency. Secondly, the PKS chose Syamsari Kitta because of his strong ability and strong support-bases in Takalar as well as positive electability with the community. While Ahmad Daeng Sere chose as a candidate for vice regent because he can raise the electability to fight the duet of incumbent. Both have in common with the idea of change to make Takalar much better. Third, the recruitment of Syamsari Kitta as a candidate for regional head / regent because he is a PKS cadre who has experience and capability in politics, his personality is known as an easy person to associate and communicate with the community. The quality of Syamsari Kitta as PKS cadres got positive electoral and militancy support from PKS cadres and other winning team